2011
DOI: 10.2753/pmr1530-9576340302
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Evaluation in Nonprofit Organizations

Abstract: This study uses organizational theory to explore why nonprofit organizations conduct evaluations and how they use evaluation information. According to rational choice theory, managers of nonprofit organizations will conduct evaluations to make sure they are making good decisions about how to improve their services and achieve their goals. Yet, according to data gathered about the experiences of 31 nonprofit organizations, this assumption about the evaluation practices of nonprofits rarely holds true. Rather, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…This scholarship has suggested a number of factors that may contribute to more effective program evaluation. For example, the funder approach or mandate can promote evaluation (Carman ; Mitchell ; Newcomer, El Baradei, & Garcia 2013; Poole, Davis, Reisman, & Nelson ), although evaluations mandated by funders without sufficient consultation with the nonprofit can lead to merely perfunctory or symbolic practices (Carman ; Gandia ; Liket, Rey‐Garcia, & Maas 2014). Indeed, research has found that program evaluation may be driven more by internal stakeholder buy‐in than by external funding availability (MacIndoe & Barman ).…”
Section: Evaluation Catalysts and Obstacles In The Nonprofit Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…This scholarship has suggested a number of factors that may contribute to more effective program evaluation. For example, the funder approach or mandate can promote evaluation (Carman ; Mitchell ; Newcomer, El Baradei, & Garcia 2013; Poole, Davis, Reisman, & Nelson ), although evaluations mandated by funders without sufficient consultation with the nonprofit can lead to merely perfunctory or symbolic practices (Carman ; Gandia ; Liket, Rey‐Garcia, & Maas 2014). Indeed, research has found that program evaluation may be driven more by internal stakeholder buy‐in than by external funding availability (MacIndoe & Barman ).…”
Section: Evaluation Catalysts and Obstacles In The Nonprofit Sectormentioning
confidence: 99%
“…The size and growth of the sector has generated increased interest in evaluating the impact of nonprofits’ programs (Mitchell ; O'Flanagan, Harold, & Brest ) and developing “rigorous” evidence of program effectiveness, beyond financial reporting and output counting. This has presented particular challenges to nonprofit organizations, many of which lack the resources and capacity to meet stakeholders’ rising expectations (Carman , , ; Carman & Fredericks ; MacIndoe & Barman ; Mitchell , a, b; Thomson ). As the accountability relationships and learning orientations of nonprofit organizations and their stakeholders continue to evolve, the nonprofit community as a whole stands to benefit from a richer understanding of nonprofit evaluation practices and the factors that may enhance or impede the ability of nonprofits to develop rigorous evidence of program impact.…”
mentioning
confidence: 99%
“…For example, scholars drawing on agency theory explain performance by evaluating the extent to which agents have expectations set by funders, as principals (Benjamin, 2010;Lambright, 2009;Van Slyke, 2007). Researchers have also used institutional theory to explain performance measurement practices, emphasizing how external forces affect organizational legitimization strategies (Carman, 2011;DiMaggio & Powell, 1983;Ebrahim, 2005). Like agency theory, resource dependence focuses on the relationship between funders and providers.…”
Section: Multiple Constituency Theorymentioning
confidence: 99%
“…Drawing on a range of organizational theories, such as resource dependence, institutionalism, and agency theory, researchers often explain performance measurement primarily in terms of measures imposed on providers by funders (Benjamin, 2010;Campbell et al, 2012;Carman, 2011;Mayhew, 2012). Although these theories are useful in explaining organizational behavior, they are incomplete.…”
Section: Implications For Theorymentioning
confidence: 99%
“…In addition, this information may assist in program evaluation and research concerning treatment efficacy or effectiveness as means of contextualizing the measured outcomes. This may function as an important funding aspect for batterer intervention programs: Program evaluations have become an important element of accountability to funders (Carman, 2011).…”
Section: The Present Studymentioning
confidence: 99%